Death and Rebirth in Late Antiquity - Jefferson, Lee M. (Lexington Books, 2022)
Death and rebirth was of vital importance to early Christians in late antiquity. In late antiquity, death was all encompassing. Mortality rates were high, plague and disease in urban areas struck at will, and one lived on the knife’s edge regarding one’s health. Religion filled a crucial role in this environment, offering an option for those who sought cure and comfort. Following death, the inhumed were memorialized, providing solace to family members through sculpture, painting, and epigraphy. This book offers a sustained interdisciplinary treatment of death and rebirth, a theme that early Christians (and scholars) found important. By analysing the theme of death and rebirth through various lenses, the contributors deepen our understanding of the early Christian funerary and liturgical practices as well as their engagement with other groups in the Empire.